The Effectiveness of Facebook Marketing in Influencing the Consumers’ Purchase Intention - Chuah, Chong Sheng (2011)
The aim of this study was the examination of an integrated model that extended the Theory of Planned Behavior (TPB) with an additional factor, trust, by investigating Malaysian Net Generations intention to shop online in Facebook. Based on a sample of 300 net generations, the study found that all the independent variables significantly influenced their intention to shop online in Facebook. The results also showed that trust can enhances the predictive utility of the TPB for the intention of engaging in shopping online in Facebook, along with the three variables (attitude, subjective norm and perceived behavioral control) of the TPB. The findings illustrated that trust factor is the most influential predictor variable of intention to shop online in Facebook, followed by attitude, perceived behavioral control and subjective norm.